Analisis Tingkat Pendapatan UMKM (Usaha Mikro,Kecil,Menengah) Terhadap Dampak COVID-19 di Kota Medan - Aini Rahma; Raina Linda Sari; Dede Ruslan (Economic Reviews Journal, 2024)
Since the end of 2019 the Covid-19 pandemic has attacked all corners of the world. The Covid-19 pandemic has had a tremendous impact on the economic sector throughout the world because many restrictions on community activities have caused the world economy to become volatile again, including the Indonesian economy, especially the city of Medan. The presence of the Covid-19 pandemic certainly presents a new challenge for Indonesia with an unprecedented spectrum and magnitude. Indonesia is also in the midst of a health and economic storm as experienced by more than 200 other countries. This extraordinary situation requires governments in various countries to devote energy and thought to producing balanced policies on the health, social and economic side. Starting from the price of petroleum which is in free fall, as well as the prices of other commodities such as gas and palm oil which will continue to be pulled down. This research aims to determine the impact of the Covid 19 pandemic on MSMEs (micro, small and medium enterprises) in the city of Medan. The research method used was a qualitative descriptive method. Where in the data collection process carried out were interviews with several MSME actors who sell in the Medan City area, such as traders who meet consumer needs, namely Primary, Secondary and Tresier. The government's decision to carry out a Social Distancing program has further worsened the situation for MSMEs, showing that the impact of Covid-19 is very influential, where in general more than 50% of MSMEs have experienced a decrease in income, reduction in employees, difficulties in borrowing bank installments. This is because people's purchasing power has decreased, resulting in the market being empty of buyers, as well as the lack of people's activities outside the home because they choose to stay at home. Several business actors are able to survive by trading through the use of technological applications that are easy and widely available for MSMEs so that they are able to expand their market network online. Even though this method cannot completely restore the income of MSMEs, especially in the city of Medan, there are still many obstacles that occur.